2022
DOI: 10.1007/s10198-022-01529-8
|View full text |Cite
|
Sign up to set email alerts
|

Does competition improve hospital performance: a DEA based evaluation from the Netherlands

Abstract: Many countries have introduced competition among hospitals aiming to improve their performance. We evaluate the introduction of competition among hospitals in the Netherlands over the years 2008–2015. The analysis is based on a unique longitudinal data set covering all Dutch hospitals and health insurers, as well as demographic and geographic data. We measure hospital performance using Data Envelopment Analysis and distinguish three components of competition: the fraction of freely negotiated services, market … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…While others detailed the model as Radial, Non-Radial and Oriented, Non-Radial and Non-Oriented, and Radial and Non-Radial [23,126]. The majority of the research that were included used Radial DEA models (72 of 89, 80.90%) [46,4852,5462,6577,79,80,8286,89–94,96100,102–116,118124,127130]. BCC, CCR or combination of both models were the specific model utilized in measuring efficiency via radial change of input and output values.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…While others detailed the model as Radial, Non-Radial and Oriented, Non-Radial and Non-Oriented, and Radial and Non-Radial [23,126]. The majority of the research that were included used Radial DEA models (72 of 89, 80.90%) [46,4852,5462,6577,79,80,8286,89–94,96100,102–116,118124,127130]. BCC, CCR or combination of both models were the specific model utilized in measuring efficiency via radial change of input and output values.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, either output expansion or input decrease is the primary evaluation goal. More than half of the studies (55.06%, 49 of 89) [4648,5054,58,60,6469,7173,7577,80,9194,96,98,99,103107,109111,113–116,118,121,124,127,128,130,135] applied input-orientated DEA models. The researchers indicated that the choice of input orientation was made to be in line with the fact that the majority of healthcare units aim to minimize inputs given a goal level of output.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations